(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
The objective of this study are to know how the proses of Tikam Dabus Dance in Ambon and what the meaning of movement Tikam Dabus Dance in Ambon.This research used a qualitative method. The research was located in Ambon East Seram Regency. The data were gathered by doing observation, and interview, and documentation. The data was obtained then described in the form of logical and systematic description supported by scientific arguments to answer the problems that exist in this study.The result of this research explain that Tikam Dabus dance is a tarekat (a way to get closer to Allah SWT) not a traditional dance. The art of Tikam Dabus Dance in Ambon is an art that shows the endurance of the dancer against sharp objects by performing dances and barjanzi music accompaniment with the hammering of a tambourine repeatedly. The result of this research also showed there are six meaning of movement Tikam Dabus Dance In Ambon East Seram Regency, namely: Worship Movement, Three Steps Movement, Shooting Movement, Meninjau Anak Dara Movement, Elang Belego Movement, Sago hitting movement.